Analysis of the Dynamics of the Basic Technical and Physical Training on Uneven Bars in Women’s Artistic Gymnastics - Valerian Nicolae, Forminte; Vlad Teodor, Grosu; Ramona, Micu; Liliana, Cosma; Vladimir, Potop (Arena-Journal of Physical Activities, 2021)
Purpose. This paper makes an analysis of the basic technical and physical training on uneven bars in women’s artistic gymnastics. Methods. A study was carried out in the Romanian national team of women’s artistic gymnastics, with a group of 14 gymnasts aged 13-16. The study was conducted from 2017 (initial testing) to 2018 (final testing). The physical training (PT) was assessed by means of 10 physical tests and the basic technical training (TT) by 8 tests. Performance capacity (PC) on uneven bars was monitored in competitions too. Statistical analysis was made with KyPlot program, using descriptive indicators and the parametric method Paired Comparison for Means, at p<0.05. Results. The comparative analysis of PT indicators highlights an improvement of muscle strength development and significant differences at p<0.05 in holding a handstand (physical test - PT3), power handstand (PT4), alternating one-legged squats (PT5), long jump (PT8) and push-ups (PT10). The comparative analysis results of basic TT indicators reveal an improved execution in final testing at p<0.001, p<0.01 and <0.05, except for elements with flight phase on the same bar (technical test - TT4) - p>0.05. The PC results highlight the elements difficulty increase (p<0.05), the execution decrease, the final score increase and p>0.05. Conclusions. The use of a physical training program (per muscle groups, both in the first and the second training) and preparatory exercises for each technical requirement on uneven bars showed the dynamics of muscle groups strength development according to the results obtained in competitions.